LINKING METAPHORS AND ARGUMENTS TO SEMANTIC PROSODIES: A CASE STUDY OF VICTORY VERBS IN INDONESIAN ONLINE FOOTBALL NEWS - Prihantoro . (Soegijapranata Catholic University, 2015)
The use of hyperbolic victory verbs such as menghancurkan to destroy, menekuk to fold, menggunduli to shave bald characterizes football news report in Indonesia. These verbs are used in the specific domain; therefore, suggesting that they need further examination. The objectives of this research are 1) to map metaphor classes and the arguments of these verbs and 2) to confirm whether the metaphor classes and the arguments are determinant to the semantic prosody of these verbs. Texts under football domainthat contain victory verbs were collected from different online news portals. The examination of victory verbs resulted on 10 affix formations and 10 different metaphor classes. Of these victory verbs, the frequent semantic roles are (the victors), (the defeated teams) and (the victories). The identification of the semantic prosody has shown that affix formation is fairly distributed and not significantly correlate to prosody. However, there is a strong tendency that metaphor class with negative nuance (like +DESTRUCTION, +WAR, +FIGHT) and the presence of an argument that takes semantic role suggests negative semantic prosody. They might be major cues to prosody in this data, but reexamination on a terminal level is still required to formalize this description, as some exceptions and irregularities are also present.